When Franco Falls. Educational Proposals for Spain from Exile (1945) - Cruz Orozco, José Ignacio; García de Fez, María Sandra (Historia y Memoria de la Educación, 2019)
After World War II in 1945, many people believed that the end of the conflict would lead to the fall of Francoism, the comeback of the Republican government and a return to democracy in Spain. This idea of the return had a significant presence in publications, meetings, manifestos and political actions, especially in Mexico and France. Education stood out among the topics addressed by the exiled groups that had a greater political and intellectual implication. The education of the new generations of Spaniards, who were supposed to resume the republican principles and values, was extremely important. This article examines three documents that include recommendations on the educational policy to be implemented after the Republican restoration. These proposals were drawn up from the republican, socialist and libertarian ethoses. This paper also reviews the initiatives carried out on French soil at that time to maintain, among the younger exiled, a Spanish identity